MODEL-BASED GREEN MANAGEMENT WITH BALANCED SCORECARD PERSPECTIVE FOR COOPERATIVES - Waluyo, Mohammad Rachman; Handoko, Fourry; Vitasari, Prima (Acta Scientiae et Intellectus, 2024)
The purpose of this research is to know the influence of balanced scorecard (BSC) variable based Green Management which sustainable and synergized with Structural Equation Modelling (SEM) as a means of planning future strategy in business process. This study uses a Likert scale with 100 samples for using maximum likelihood estimation technique to formulate 6 hypotheses based on the BSC perspective, excellence Green Management. The results showed 4 significant variables and 2 not significant variables, learning variable (X1) is not significant to Internal Business Process (Y1) and Green Management (Y4) is not significant to Sustainable Competitive Advantage (Y6) with mathematics model equations as follows Y5 = 0.07 X1 + 0.15 X2, the process of mathematical equations through three processes namely measurement, structural and modification.